For better or worse: crosstalk of parvovirus and host DNA damage response - Chen, Songbiao; Liu, Feifei; Yang, Aofei; Shang, Ke (Frontiers in Immunology, 2024)
Parvoviruses are a group of non-enveloped DNA viruses that have a broad spectrum of natural infections, making them important in public health. NS1 is the largest and most complex non-structural protein in the parvovirus genome, which is indispensable in the life cycle of parvovirus and is closely related to viral replication, induction of host cell apoptosis, cycle arrest, DNA damage response (DDR), and other processes. Parvovirus activates and utilizes the DDR pathway to promote viral replication through NS1, thereby increasing pathogenicity to the host cells. Here, we review the latest progress of parvovirus in regulating host cell DDR during the parvovirus lifecycle and discuss the potential of cellular consequences of regulating the DDR pathway, targeting to provide the theoretical basis for further elucidation of the pathogenesis of parvovirus and development of new antiviral drugs.